Digitalisasi Operasional Pada Asuransi Syariah - Nurhayati Harahap; Habib Hardimi Prahalim; Fadilla Fadwa Zailani Tumanggor; Nurcholiza Adha (Journal Of Informatics And Busisnes, 2026)
Operational digitalization is one of the key strategies for improving efficiency and service quality in the financial industry, including Islamic insurance. This study aims to analyze the implementation of operational digitalization in Islamic insurance, the benefits obtained, and the challenges faced during its implementation process. The research method used is a descriptive qualitative approach with a literature study technique, through data collection from books, journals, official reports, and related regulations. The results show that operational digitalization is able to enhance administrative efficiency, accelerate participant services, facilitate contribution payments, policy management, and online claim submissions. In addition, digitalization supports transparency in managing participants’ funds in accordance with Sharia principles, thereby increasing public trust. However, the implementation of digitalization still faces several challenges, such as data security issues, limited human resources, and low digital literacy among the public. Therefore, Islamic insurance companies need to develop appropriate technological innovations while adhering to Sharia principles in order to improve competitiveness and expand market reach in the digital era.